Prevalence And Pattern Sensitivity Multidrug Antibiotics Resistant Pseudomonas aeruginosa in the High Care Unit at Dr. Soetomo General Academic Hospital Period 2022-2023 - Kusumawati, Ratna; Koendhori, Eko Budi; Mertaniasih, Ni Made; Ikhwani, Irfan Arif; Hidayat, Dimas Firman; Levani, Yelvi; Paramitha, Ayu Lidya (Universitas Muhammadiyah Surabaya, 2024)
The prevalence of Multidrug antibiotic-resistant Pseudomonas aeruginosa (MDRPA) has been increasing during the decade And has become attention in hospital patients. This retrospective descriptive descriptive aimed to determine the prevalence of MDRPA and its sensitivity patterns. Data were taken from results of bacterial culture and antibiotic resistance tests from various clinical specimens from patients at Dr. Soetomo General Academic Hospital throughout 2022-2023. The resistance test was carried out using a Vitek 2 compact instrument. MDRPA is defined as Pseudomonas aeruginosa that is not sensitive to three or more of the following classes of antibiotics: meropenem or imipenem, ciprofloxacin, gentamicin or amikacin, ceftazidime or cefepime, and piperacillin/ tazobactam. The prevalence of MDRPA was 57.0%. MDRPA isolates were also the most common origin from the burn unit and HCU A (high care unit A), mostly from pus specimens and sputum. Pseudomonas aeruginosa sensitivity was best with piperacillin/tazobactam (55.5%), meropenem (54.8%), amikacin (47.5%), gentamicin (46.5%), cefepime (46.3%), ceftazidime (45.0%), ciprofloxacin (44.7%) and aztreonam (43.2%). The sensitivity of MDRPA to antibiotics is much lower than that of Pseudomonas aeruginosa. This study showed high number of MDRPA specifically in Surabaya and the pattern sensitivity of Pseudomonas aeruginosa can become guidelines in choosing antibiotics treatment for patients.